Numerical Study of Composite Concrete Castellated Double Channel Beams with Strengthening Techniques (Journal of Engineering, 2024)
Current numerical research was devoted to investigating the effect of castellated steel beams without and with strengthening. The composite concrete asymmetrical double hot rolled steel channels bolted back to back to obtain a built-up I-shape form are used in this study. The top half part of the steel is smaller than the bottom half part, and the two parts were connected by bolting and welding. The ABAQUS/2019 program employed the same length and conditions of loading for four models: The first model is the reference without castellated and strengthening; the second model was castellated without strengthened; the third model was castellated and strengthened with reactive powder concrete encased in the steel web, and the fourth model was castellated and strengthened with reactive powder concrete and lacing steel rebar's welded diagonally on two sides of the steel web. According to the Numerical results, there was an increase in ultimate load capacity compared to the reference model of about 22.74%, 51.65%, and 77.98% in the second, third, and fourth models, respectively; also, there is a reduction in deflection of 55.52%, 58.74, and 60.55% in the second, third, and fourth models, respectively, compared to the level deflection at ultimate load for the reference model, with an increase in stiffness and ductility. In comparison to the I section, the fabrication of a castellated steel beam from the double channel is more cost-effective in terms of cutting steel loss at the ends of the castellated beam, this is due to the feature of rotation and reflection of the steel channel section during cutting and forming to castellated shape.